Acute Digital Ischemia After Arterial Injection of Crushed Zolpidem Tablets: Role of Microcrystalline Cellulose? A Case Report - Détriché, Grégoire; Goudot, Guillaume; Khider, Lina; Galloula, Alexandre; Guillet, Matthieu; Lillo-Le Louët, Agnès; Messas, Emmanuel; Mirault, Tristan (Frontiers in Pharmacology, 2020)
Literature is scarce on acute ischemia after intra-arterial injection of crushed tablets and no effective medical treatment against the progression of lesions is reported. The only factor able to modify the outcome is the delay between injection and management by a specialized vascular team. Moreover the risk of necrosis seems higher after benzodiazepine intra-arterial injection than with other drugs. We tried to find out mechanistic explanations. We report on the case of a 31-year-old drug addict woman who self-injected into her left brachial artery crushed tablets of zolpidem. She developed an acute ischemia of the left hand, with necrosis of the intermediate and distal phalanges of fingers II, III, and IV. Angiogram of the left upper arm confirmed the distal arterial occlusions with no run-off after the palmar arch in the necrotic fingers. Once she was admitted into our vascular unit, intravenous vasodilator therapy by iloprost, heparin and local protective care were rapidly introduced. After delineation between living and necrotic tissues, she required distal amputations of the affected fingers. The clinical severity of arterial injections of benzodiazepine tablets is linked to the association of several pathophysiological mechanisms. Rather than related benzodiazepine pharmacologic effects with tissue ischemia, by the inhibition of phosphodiesterase, a vasodilator intermediate, or through the peripheral benzodiazepine-type receptor, the predominant mechanism is more likely in relation with microcrystalline cellulose, one component of zolpidem tablets, known as potential embolic agents. They are insoluble and resistant to degradation in water. These properties are probably prominent in the case we described here. Through this case report we want to drag attention of physicians in charge of a patient with acute ischemia after crushed tablet accidental intra-arterial injection, not only to look at the drug injected but also the other components of the tablet and especially to microcrystalline cellulose.